Keeper of the King's Peace: Colonel G.E. Sanders and the Calgary Police Magistrate's Court, 1911-1932 - Thorner, Thomas; Watson, Neil (Urban History Review / Revue d'histoire urbaine, 1984)
Canadian historians have shown limited interest in the legal development of the lower courts. The history of Calgary's police court and in particular, the administration of G.E. Sanders reveals much about the development of the office and urban society since many issues of popular concern came into focus through legal action. As fear about crime and even anarchy grew with the steady influx of immigrants, the police court assumed a special significance. Gradually at first and then with rapid strides it emerged as a powerful bulwark of conservative defence.